THE ROLE OF RADIATION DIAGNOSTIC TECHNIQUES IN THE DIAGNOSIS OF CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION - E. A. Mershina; V. E. Sinitsyn (Атеротромбоз, 2016)
The article is an overview of a diagnostic algorithm and capabilities  of different imaging techniques  in the diagnosis of chronic thromboembolic pulmonary  hypertension (CTEPH). The authors touch upon imaging approaches specific for CTEPH and idiopathic pulmonary  hypertension.  The results of comparative studies of diagnostic  accuracy  of multislice computed  tomography,  ventilation/perfusion scintigraphy,  angiography,  and comparative characteristics of the methods, are described. A new method, dual-energy computed  tomography, used in the diagnosis of CTEPH and for determining indications  for surgical treatment, is highlighted.